Study on Ba Element Solidified by Alkaline Heat Treatment in Oil-based Cuttings - Yang, Rui; Chen, Ye; Liu, Tao; Zheng, Nenghong (International Journal of Materials Science and Technology Studies, 2024)
Oil-based cuttings from a shale gas well were studied. The effect of reaction temperature and holding time on curing effect of Ba element in oil-based cuttings by heat treatment method. The experimental results show that the addition of NaOH can effectively solidify Ba element in oil-based cuttings during heat treatment. At the same time, with the increase of reaction temperature, the increase of the proportion of NaOH and the increase of holding time, the leaching amount of Ba was lower and lower.